2018
DOI: 10.1158/1078-0432.ccr-17-2855
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Chemotherapeutic Efficacy in Non–Small Cell Lung Cancer by Serum Metabolomic Profiling

Abstract: In clinical practice, there are currently no validated biomarkers that can, prior to treatment, reliably indicate the intrinsically sensitive or resistant features of a non-squamous NSCLC patient to pemetrexed plus platinum doublet chemotherapy. In this study, we investigated the metabolic characteristics of a large cohort of pre-chemotherapeutic serum samples (354 cases) and found tight associations between small metabolite subsets and the responses of patients to this cytotoxic drug combination. We develo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 43 publications
1
41
0
Order By: Relevance
“…Yang et al found 25 different lipid metabolites, including PE, between malignant pleural effusion (MPE) and benign pleural effusion (NPE), indicating that lipid metabolites may be used to partition MBE and BPE [44]. In our study, PE One Study showed that L-palmitoylcarnitine is signi cantly reduced in advanced lung cancer patients [46]. In another study, the level of palmitoylcarnitine was lower in the hepatocellular carcinoma group than in the cancer-free control group, and blood acylcarnitine levels may be in uenced by hepatic fatty acid metabolism, in other words, decreased acylcarnitine levels may re ect the decreased production of acyl groups in the liver or other tissues.…”
Section: Discussionsupporting
confidence: 51%
“…Yang et al found 25 different lipid metabolites, including PE, between malignant pleural effusion (MPE) and benign pleural effusion (NPE), indicating that lipid metabolites may be used to partition MBE and BPE [44]. In our study, PE One Study showed that L-palmitoylcarnitine is signi cantly reduced in advanced lung cancer patients [46]. In another study, the level of palmitoylcarnitine was lower in the hepatocellular carcinoma group than in the cancer-free control group, and blood acylcarnitine levels may be in uenced by hepatic fatty acid metabolism, in other words, decreased acylcarnitine levels may re ect the decreased production of acyl groups in the liver or other tissues.…”
Section: Discussionsupporting
confidence: 51%
“…Circulating-metabolite-based prognostic models have previously been shown to have its promising clinical applications in several cancers, such as glioblastoma (34), non-small cell lung cancer (35), and esophageal adenocarcinoma (24). However, the previous metabolomic studies of ESCC solely focused on the diagnostic value of the metabolites and rarely assessed their prognostic significance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, metabolomics provides insight into outcomes of transcription changes, which reflect differential functionality of specific metabolites influencing the tumor response. Attempts to predict therapy response based on metabolomics analysis only (Tian et al, 2018) or gene expression (Geeleher and Cox, 2014) yield results typically relying on statistical analyses that do not necessarily represent any particular tumor (Peng et al, 2018;Mucaki et al, 2019). Ideally, a mathematical-based framework would be capable of recreating particular patients' tumors for in silico prediction of behavior in time and space prior to treatment, incorporating omics data for patient customization, and thus move toward the goal of predictive personalized treatment.…”
Section: Mathematical Modeling Provides a Link To The Molecular Scalementioning
confidence: 99%